A new energy tire and production method thereof
By using the rubber layer and fibrous woven layer in the suction layer of new energy tires, and adding boron nitrite/aluminum aluminum microspheres, the problem of poor thermal a thermal a thermal conductivity and the low mechanical strength of the tires are solved. Longer life.
Patent Information
- Application Number
- CN202411676492.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The sound-absorbing layer materials of existing new energy tires have poor thermal conductivity, which causes the tires to be in a high-temperature state for a long time when driving at high speed, affecting performance and service life. At the same time, the material has low mechanical strength and is prone to aging, which increases maintenance costs.
The sound absorption layer consisting of the rubber layer and the fiber fabric layer is covered with the surface of the fiber fabric layer, and the boron nitride/alumina microsphere is added to the rubber layer and the fiber fabric layer to improve the sound absorption and thermal conductivity. The fiber woven layer is woven by the aramid fiber and the hollow polyurethane fiber, which combines the excellent sound absorption performance of polyurethane fibers to form a closed and empty cavity to improve the sound absorption effect.
The sound absorption effect and thermal conductivity of new energy tires are significantly improved, the service life of the tire is prolonged, the maintenance cost is reduced, and driving comfort is improved.
Smart Images

Figure CN119189564B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of automobile tire production, and in particular to a new energy tire and a production method thereof. Background Art
[0002] The patterns of new energy tires are complex and the material is relatively hard. In addition, the body weight of new energy vehicles is relatively large. Therefore, when new energy tires are driving at high speeds, the tire noise generated by the friction between the tires and the road surface is large. It is necessary to set a sound-absorbing layer in the new energy tires to reduce the tire noise and improve driving comfort.
[0003] The patent with application number 201910267714.1 discloses a tire noise reduction device and its production method, which adopts the method of installing a silent layer structure with a staggered layout inside the tire to absorb and reduce the internal air vibration noise caused by the contact between the tread and the road surface due to high-speed driving. The tire noise reduction device includes a base belt, on which at least one group of silent layers is bonded, and each group of silent layers is evenly arranged along the longitudinal interval of the base belt; the silent layer has a structure formed by superimposing two layers of polyurethane foam material, and feather tail edge-like serrated protrusions are evenly arranged on the other end faces except those bonded to the base belt. The polyurethane foam material of the silent layer itself has a porous structure, and the silent layer has several bionic cotton blocks of different sizes, which are bonded to the inner side of the vulcanized tire embryo through a special high-temperature resistant and flame-retardant adhesive fixative, so that it can absorb the energy generated by the vibration of the inner cavity air and achieve the purpose of noise reduction. However, this technical solution has the following problems:
[0004] 1. Polyurethane foam material can convert vibration energy into heat energy and has good sound absorption effect, but its thermal conductivity is poor. When the tire is driving at high speed, the heat generated by the friction with the road surface is superimposed on the heat converted from noise, which will keep the tire in a high temperature state for a long time, affecting the performance and service life of the tire;
[0005] 2. The mechanical strength of polyurethane foam material itself is low. When it is pasted inside the tire, it will reduce the overall mechanical properties of the tire;
[0006] 3. The polyurethane foam material is directly exposed to the air and is continuously heated when the tire is running, which makes it very easy to turn yellow and age, resulting in a short service life, which increases the maintenance cost of the tire.
[0007] In summary, there is an urgent need to provide a new energy tire with good sound absorption, good thermal conductivity, high mechanical strength and low maintenance cost. Summary of the invention
[0008] In order to solve at least one of the above technical problems, the present invention provides a new energy tire, including a tire body, the inner wall of the tire body is circumferentially bonded with a sound-absorbing layer, the sound-absorbing layer includes a rubber layer and a fiber fabric layer, the rubber layer is coated on the surface of the fiber fabric layer, and S-shaped grooves are equidistantly arranged at the circumference of the joint with the tire body; the fiber fabric layer includes hollow meta-aramid fibers and hollow polyurethane fibers, the rubber layer, the hollow meta-aramid fibers and the hollow polyurethane fibers all contain boron nitride / alumina microspheres, and the boron nitride / alumina microspheres are hollow microspheres with a core-shell structure with hollow glass microspheres as cores and boron nitride / alumina as shells.
[0009] In the above technical scheme, the tire body can directly adopt the new energy tire substrate without sound-absorbing cotton in the prior art; the matrix material formula of the rubber layer is not limited, and it is preferred to adopt a material formula close to the inner liner of the tire, the rubber layer can seal the fiber fabric layer, and the S-shaped groove on the rubber layer can absorb sound and reduce noise. The rubber layer is sealed and coated on the surface of the fiber fabric layer, which can not only prevent the polyurethane fiber from being oxidized and degraded, and increase the service life of the polyurethane fiber, but also make the weaving holes in the fiber fabric layer, the hollow cavity of the meta-aramid fiber and the hollow cavity of the polyurethane fiber form a closed cavity. Since the closed cavity has a much higher absorption effect on low-frequency noise than the open cavity, and the tire noise of the tire is mainly low-frequency noise, the absorption effect of the sound-absorbing layer on tire noise can be greatly improved; the hollow meta-aramid and Hollow polyurethane fibers can be prepared by using any suitable meta-aramid spinning solution and polyurethane spinning solution in the prior art in combination with coaxial spinning technology. Meta-aramid fibers have excellent mechanical properties and can greatly improve the service life of the sound-absorbing layer. Polyurethane fibers have excellent sound absorption performance and can greatly improve the sound absorption effect of the sound-absorbing layer. The boron nitride / aluminum oxide microspheres in the rubber layer and the fiber fabric layer can absorb sound and conduct heat, thereby improving the thermal conductivity of the sound-absorbing layer. The boron nitride / aluminum oxide microspheres use hollow glass microspheres as the core to obtain a core structure with a closed cavity, thereby improving the absorption effect of tire noise. Using boron nitride / aluminum oxide as the core, a shell structure with high thermal conductivity can be obtained. In addition, boron nitride and alumina themselves have a large number of pores, which can further improve the sound absorption effect.
[0010] Preferably, the rubber layer comprises an inner layer, an outer layer and two side edges, the S-shaped groove extends along the width direction of the inner layer, the depth is 1 / 2 to 2 / 3 of the thickness of the inner layer, the width is 1 to 3 mm, and the distance between two adjacent S-shaped grooves is 3 to 10 mm; the thickness ratio of the inner layer, the outer layer, the side edge and the fiber fabric layer is (1 to 3): 1: 1: (3 to 20), the average pore size of the woven holes of the fiber fabric layer is 2 to 200 μm, and the density is 0.02 to 0.2 g / cm 3The mass ratio of the hollow meta-aramid fiber to the hollow polyurethane fiber is (1-3):3; the rubber layer, the hollow meta-aramid fiber and the hollow polyurethane fiber respectively contain 5-20wt% of boron nitride / alumina microspheres; the mass ratio of boron nitride, alumina and hollow glass microspheres in the boron nitride / alumina microspheres is 1:4:(3-4).
[0011] The present invention provides a method for producing a new energy tire, comprising the following steps:
[0012] Step S100. The rubber matrix, boron nitride / aluminum oxide microspheres, zinc oxide, stearic acid, an antioxidant and a vulcanizing agent are uniformly mixed to obtain a mixed rubber;
[0013] Step S200. Adding boron nitride / alumina microspheres to the meta-aramid spinning solution, and coaxially spinning with the meta-aramid support solution to obtain hollow meta-aramid fibers; adding boron nitride / alumina microspheres to the polyurethane spinning solution, and coaxially spinning with the polyurethane support solution to obtain hollow polyurethane fibers; weaving the hollow meta-aramid fibers and the hollow polyurethane fibers to obtain a fiber fabric layer;
[0014] Step S300. The mixed rubber is coated on the surface of the fiber fabric layer, placed in a mold with an S-shaped protrusion, and hot-pressed and vulcanized to obtain a sound-absorbing layer composed of a rubber layer covering the fiber fabric layer, wherein an S-shaped groove is provided on the outer end surface of the inner layer of the rubber layer;
[0015] Step S400: Spray adhesive on the circumferential inner wall of the tire body, and then bond the sound absorbing layer to the inner wall of the tire body to obtain a new energy tire.
[0016] In the above technical scheme, the material formula of the rubber matrix is not limited, and any suitable rubber material in the prior art can be used alone or in combination; the mixing process of the mixed rubber is not limited, and a two-stage mixing process is preferably adopted; the formulas of the meta-aramid spinning solution, meta-aramid supporting solution, polyurethane spinning solution and polyurethane supporting solution are not limited, and any suitable spinning solution and supporting solution in the prior art can be used for coaxial spinning.
[0017] Preferably, in step S100, the rubber matrix is at least one of natural rubber, butadiene rubber, butyl rubber, styrene-butadiene rubber and nitrile rubber; the antioxidant is at least one of antioxidant 4020, antioxidant H and antioxidant D; and the vulcanizing agent is sulfur;
[0018] During mixing, first mix the rubber matrix, hexagonal boron nitride, nano-aluminum oxide, zinc oxide, stearic acid and antioxidant at 60-110°C for 10-15 minutes, then add the vulcanizing agent, control the temperature at 30-40°C, and continue mixing for 5-10 minutes.
[0019] Preferably, in step S100, the mass ratio of the rubber matrix, boron nitride / aluminum oxide microspheres, zinc oxide, stearic acid, antioxidant and vulcanizing agent is 100: (6-26): (1-2): (1-3): (1-2): (1-2);
[0020] In step S200, the mass ratio of the hollow meta-aramid fiber to the hollow polyurethane fiber is (1-3):3.
[0021] Preferably, in step S100 and step S200, the preparation of the boron nitride / aluminum oxide microspheres comprises the following steps:
[0022] Step S110. sequentially performing dopamine modification and silver ion modification on the hollow glass microspheres to obtain secondary modified microspheres;
[0023] Step S120. Add the citric acid aqueous solution to the aluminum nitrate aqueous solution, stir evenly, then add the sodium hydroxide aqueous solution, stir evenly to obtain a first dispersion; add hexagonal boron nitride and secondary modified microbeads to the first dispersion, stir and disperse evenly to obtain a second dispersion; heat the liquid paraffin oil to 55-65° C., then drop the second dispersion into the liquid paraffin oil under stirring, raise the temperature to 90° C. after the dropwise addition is completed, react for 3 hours, and after the reaction is completed, separate and filter to obtain precursor particles;
[0024] Step S130: calcine the precursor particles at 450°C for 4 hours, then heat to 700°C for 8 hours, and finally calcine at 1200°C under nitrogen protection for 2 hours to obtain boron nitride / aluminum oxide microspheres.
[0025] In the above technical scheme, the dopamine modification and silver ion modification of the hollow glass microspheres can be modified by any suitable modification process in the prior art. The surface activity of the modified hollow glass microspheres is greatly improved, which can improve the adhesion stability of hexagonal boron nitride and aluminum oxide on their surfaces; the second dispersion is added dropwise to liquid paraffin oil for reaction, so as to form precursor particles with uniform particle size.
[0026] Preferably, the specific steps of step S110 include:
[0027] Step S111. Immerse the hollow glass microspheres in a dopamine hydrochloride solution with a pH value of 8.5 and a concentration of 2 g / L, stir and react at 40° C. for 24 hours, wash and filter after the reaction to obtain primary modified microspheres;
[0028] Step S112: Immerse the primary modified microbeads in a 0.05 mol / L silver nitrate solution, stir and react for 1.5 h, wash and filter after the reaction to obtain secondary modified microbeads.
[0029] Preferably, in step S110, the hollow glass microspheres are at least one of K37, K90, K85, HX0.35, and HX0.38;
[0030] In step S120, the mass ratio of citric acid, aluminum nitrate, sodium hydroxide, hexagonal boron nitride and secondary modified microbeads is 10:18:8:20:(15-20); the concentration of the citric acid aqueous solution is 40wt%, the concentration of the aluminum nitrate aqueous solution is 30wt%, and the concentration of the sodium hydroxide aqueous solution is 25wt%; the mass ratio of the second dispersion and liquid paraffin is 1:(4-5).
[0031] Preferably, in step S200, the preparation of the hollow meta-aramid fiber and the hollow polyurethane fiber comprises the following steps:
[0032] Step S210. Under nitrogen protection, m-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole are added to dimethylacetamide, and stirred to obtain a first solution; under nitrogen protection at -25 to -15°C, isophthaloyl chloride is added to the first solution in multiple portions to react, the reaction temperature is controlled to be lower than 60°C, and after the reaction is completed, the pH value is adjusted to 6 to 8 to obtain an aramid polymer solution;
[0033] Step S220. The aramid polymer solution, calcium chloride, polyethylene glycol 2000, boron nitride / alumina microspheres and dimethylacetamide are stirred and mixed uniformly, and a meta-aramid spinning solution is obtained after vacuum degassing; dimethylacetamide, ethanol and deionized water are mixed and stirred uniformly to obtain a meta-aramid support solution;
[0034] Step S230. Add the meta-aramid spinning solution and the meta-aramid supporting solution into a syringe with a coaxial needle respectively, and inject them into a coagulation bath at 60-80° C. through the syringe for coaxial spinning to obtain aramid primary fibers; wash and dry the aramid primary fibers to obtain hollow meta-aramid fibers containing boron nitride / alumina microspheres;
[0035] Step S240. Polytetramethylene glycol 2000, polycarbonate diol, 1,4-butanediol, bis(2-hydroxyethyl) disulfide and isophorone diisocyanate are stirred and reacted at 60-90° C. for 1-1.5 hours, and then cooled to 40-50° C. to obtain a prepolymer;
[0036] Step S250. Stir the prepolymer, polycarbodiimide, boron nitride / alumina microspheres, polyvinyl pyrrolidone and ethyl acetate at 20-40° C. for 1-1.5 hours to obtain a polyurethane spinning solution; mix and stir the ethyl acetate and polyvinyl pyrrolidone to obtain a polyurethane support solution;
[0037] Step S260. Add the polyurethane spinning solution and the polyurethane supporting solution into a syringe with a coaxial needle respectively, and inject them into a coagulation bath at 50-70° C. through the syringe for coaxial spinning to obtain polyurethane primary fibers; after washing and drying the polyurethane primary fibers, hollow polyurethane fibers containing boron nitride / alumina microspheres are obtained.
[0038] In the above technical scheme, meta-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and isophthaloyl chloride are reacted together to obtain a meta-aramid spinning solution containing imidazole groups. The imidazole groups can complex boron nitride / alumina microspheres, improve the bonding stability between boron nitride / alumina microspheres and meta-aramid, and improve the overall structural strength and thermal conductivity stability. Polytetramethyleneimine ether diol 2000, polycarbonate diol, 1,4-butanediol, bis(2-hydroxyethyl) disulfide and isophorone diisocyanate are used to prepare a prepolymer, so as to obtain a polyurethane fiber with self-repairing function, thereby improving the service life of the polyurethane fiber.
[0039] Preferably, in step S210, the molar ratio of m-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and dimethylacetamide is (6-7): (3-4): (60-80); the molar ratio of the sum of the moles of m-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to isophthaloyl chloride is 1:1; the concentration of the aramid polymer in the aramid polymer solution is 33-38wt%;
[0040] In step S220, the mass ratio of aramid polymer solution, calcium chloride, polyethylene glycol 2000, boron nitride / alumina microspheres and dimethylacetamide is 15:1:1:(0.5-1.5):(20-25); the mass ratio of dimethylacetamide, ethanol and deionized water is 60:10:30;
[0041] In step S230, the coaxial needle model is 22G / 17G, and the injection speed is 0.03mm / s; the coagulation bath contains 20wt% DMF and 80wt% deionized water; the hollow meta-aramid fiber contains 5-20wt% boron nitride / alumina microspheres;
[0042] In step S240, the mass ratio of polytetramethylene glycol 2000, polycarbonate glycol, 1,4-butanediol, bis(2-hydroxyethyl) disulfide and isophorone diisocyanate is (60-70):(5-10):(0.5-1):(1-3):40;
[0043] In step S250, the mass ratio of the prepolymer, polycarbodiimide, boron nitride / alumina microspheres, polyvinyl pyrrolidone and ethyl acetate in the spinning solution is 15: (0.5-1): (1.5-4): (1-2): (20-30); the mass ratio of ethyl acetate and polyvinyl pyrrolidone in the spinning core solution is 2:1;
[0044] In step S260, the coaxial needle model is 22G / 17G, the injection speed is 0.03 mm / s; the coagulation bath is deionized water; and the hollow polyurethane fiber contains 5 to 20 wt% of boron nitride / alumina microspheres.
[0045] Compared with the prior art, the present invention has the following beneficial technical effects:
[0046] 1. The sound-absorbing layer of the new energy tire is composed of a rubber layer and a fiber fabric layer. Hollow boron nitride / alumina microspheres are added to the rubber layer and the fiber fabric layer. Boron nitride / alumina microspheres can absorb sound and conduct heat, thereby improving the sound absorption and thermal conductivity of the sound-absorbing layer, improving driving comfort, and extending the service life of the tire;
[0047] 2. The fiber fabric layer is woven from hollow meta-aramid fibers and hollow polyurethane fibers, and has a large number of woven holes. The hollow structure of meta-aramid fibers and polyurethane fibers and the excellent sound absorption ability of polyurethane fibers themselves can greatly improve the sound absorption and noise reduction effect of the sound-absorbing layer. In addition, meta-aramid fibers have excellent mechanical properties, and after being woven with polyurethane fibers, the mechanical properties and service life of the sound-absorbing layer can be greatly improved.
[0048] 3. The S-shaped grooves on the rubber layer can absorb and reduce noise. The rubber layer is sealed and coated on the surface of the fiber fabric layer, which can form a closed cavity among the weaving holes in the fiber fabric layer, the hollow cavity of the meta-aramid fiber and the hollow cavity of the polyurethane fiber, thereby improving the absorption effect of the sound-absorbing layer on tire noise and preventing the polyurethane fiber from being oxidized and degraded, thereby increasing the service life of the sound-absorbing layer and reducing maintenance costs.
[0049] In summary, the new energy tire provided by the present invention has good sound absorption effect, good thermal conductivity, high mechanical strength and low maintenance cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 It is a structural schematic diagram of the present invention;
[0051] Figure 2 Schematic diagram of the structure inside the rubber layer.
[0052] Description of reference numerals:
[0053] 1. Tire body, 2. Sound absorbing layer, 21. Rubber layer, 211. Inner layer, 212. Outer layer, 213. Side, 22. Fiber fabric layer. DETAILED DESCRIPTION
[0054] The specific implementation of the present invention is described below in conjunction with the accompanying drawings and embodiments:
[0055] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so that people familiar with this technology can understand and read them, and are not used to limit the conditions under which the present invention can be implemented. Any structural modification, change in proportional relationship or adjustment of size should fall within the scope of the technical contents disclosed in the present invention without affecting the effects and purposes that can be achieved by the present invention.
[0056] At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" cited in this specification are only for the convenience of description and are not used to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of the present invention without substantially changing the technical content. Example 1
[0057] Combined with Figure 1-2 The present embodiment provides a new energy tire, comprising a tire body 1, wherein a sound absorbing layer 2 is bonded circumferentially on the inner wall of the tire body 1, wherein the sound absorbing layer 2 comprises a rubber layer 21 and a fiber fabric layer 22, wherein the rubber layer 21 is coated on the surface of the fiber fabric layer 22, and an S-shaped groove is equidistantly arranged at the circumference of the part in contact with the tire body 1; the fiber fabric layer 22 comprises hollow meta-aramid fibers and hollow polyurethane fibers, wherein the rubber layer 21, the hollow meta-aramid fibers and the hollow polyurethane fibers all contain boron nitride / alumina microspheres, wherein the boron nitride / alumina microspheres are hollow microspheres with a core-shell structure having hollow glass microspheres as cores and boron nitride / alumina as shells.
[0058] The rubber layer 21 includes an inner layer 211, an outer layer 212 and two side edges 213. The S-shaped groove extends along the width direction of the inner layer 211, with a depth of 1 / 2 to 2 / 3 of the thickness of the inner layer 211, a width of 1 to 3 mm, and a distance between two adjacent S-shaped grooves of 3 to 10 mm. The thickness ratio of the inner layer 211, the outer layer 212, the side edges 213 and the fiber fabric layer 22 is (1 to 3): 1: 1: (3 to 20). The average pore size of the woven holes of the fiber fabric layer 22 is 2 to 200 μm, and the density is 0.02 to 0.2 g / cm 3The mass ratio of the hollow meta-aramid fiber to the hollow polyurethane fiber is (1-3):3; the rubber layer 21, the hollow meta-aramid fiber and the hollow polyurethane fiber respectively contain 5-20wt% of boron nitride / alumina microspheres; the mass ratio of boron nitride, alumina and hollow glass microspheres in the boron nitride / alumina microspheres is 1:4:(3-4). Example 2
[0059] Combined with Figure 1-2 This embodiment produces a new energy tire, including the following steps:
[0060] The hollow glass microspheres K37 were immersed in a dopamine hydrochloride solution with a pH value of 8.5 and a concentration of 2 g / L, and stirred at 40°C for 24 h. After the reaction, they were washed and filtered to obtain primary modified microspheres. The dopamine-modified microspheres were immersed in a 0.05 mol / L The mixture was added to a silver nitrate solution and stirred for 1.5 hours. After the reaction, the mixture was washed and filtered to obtain secondary modified microbeads. 25 parts by mass of a 40wt% citric acid aqueous solution was added to 60 parts by mass of a 30wt% aluminum nitrate aqueous solution, and after stirring, 32 parts by mass of a 25wt% sodium hydroxide aqueous solution was added, and after stirring, a first dispersion was obtained. 20 parts by mass of hexagonal boron nitride and 15 parts by mass of secondary modified microbeads were added to the first dispersion, and the second dispersion was obtained after stirring and dispersing. 750 parts by mass of liquid paraffin oil was heated to 55-65°C, and then the second dispersion was added dropwise to the liquid paraffin oil under stirring. After the addition was completed, the mixture was heated to 90°C and reacted for 3 hours. After the reaction was completed, the precursor particles were separated and filtered to obtain the precursor particles. The precursor particles were calcined at 450°C for 4 hours, then heated to 700°C for 8 hours, and finally calcined at 1200°C under nitrogen protection for 2 hours to obtain boron nitride / alumina microspheres.
[0061] Under nitrogen protection, 6 molar parts of m-phenylenediamine and 4 molar parts of 2-(4-aminophenyl)-5-aminobenzimidazole are added to 70 molar parts of dimethylacetamide, and stirred to obtain a first solution; 10 molar parts of isophthaloyl chloride are added to the first solution three times at -25 to -15°C and under nitrogen protection to react, the reaction temperature is controlled to be lower than 60°C, and the pH value is adjusted to 6 to 8 after the reaction is completed to obtain an aramid polymer solution with a polymer content of 36.98wt%; 15 parts by mass of the aramid polymer solution, 1 part by mass of calcium chloride, 1 part by mass of polyethylene glycol 2000, 0.62 parts by mass of boron nitride / alumina microspheres and 20 parts by mass of dimethyl The invention discloses a method for preparing a method for preparing a meta-aramid fiber. The method comprises the steps of: stirring and mixing dimethylacetamide and obtaining a meta-aramid spinning solution after vacuum degassing; mixing and mixing 60 parts by weight of dimethylacetamide, 10 parts by weight of ethanol and 30 parts by weight of deionized water to obtain a meta-aramid supporting solution; respectively adding the meta-aramid spinning solution and the meta-aramid supporting solution into a syringe with a 22G / 17G coaxial needle, injecting the syringe into a coagulation bath (containing 20wt% of DMF and 80wt% of deionized water) at a temperature of 60 to 80°C at a speed of 0.03mm / s for coaxial spinning to obtain aramid primary fibers; washing and drying the aramid primary fibers to obtain hollow meta-aramid fibers containing 10.05wt% of boron nitride / alumina microspheres.
[0062] 70 parts by mass of polytetramethylene glycol 2000, 10 parts by mass of polycarbonate diol, 1 part by mass of 1,4-butanediol, 2 parts by mass of bis(2-hydroxyethyl) disulfide and 40 parts by mass of isophorone diisocyanate were stirred and reacted at 60-90° C. for 1-1.5 hours, and then cooled to 40-50° C. to obtain a prepolymer; 15 parts by weight of prepolymer, 1 part by weight of polycarbodiimide, 1.78 parts by weight of boron nitride / alumina microspheres, 2 parts by weight of polyvinyl pyrrolidone and 30 parts by weight of ethyl acetate are stirred and reacted at 20-40° C. for 1-1.5 hours to obtain a polyurethane spinning solution; 20 parts by weight of ethyl acetate and 10 parts by weight of polyvinyl pyrrolidone are mixed and stirred uniformly to obtain a polyurethane support solution; the polyurethane spinning solution and the polyurethane support solution are respectively added into a syringe with a 22G / 17G coaxial needle, and injected into a coagulation bath (deionized water) at 50-70° C. at a speed of 0.03 mm / s through the syringe for coaxial spinning to obtain polyurethane primary fibers; after washing and drying the polyurethane primary fibers, hollow polyurethane fibers containing 10.01wt% of boron nitride / alumina microspheres are obtained.
[0063] 60 parts by weight of natural rubber, 15 parts by weight of butadiene rubber, 15 parts by weight of butyl rubber, 5 parts by weight of styrene-butadiene rubber and 5 parts by weight of nitrile rubber, 12 parts by weight of boron nitride / alumina microspheres, 2 parts by weight of zinc oxide, 1 part by weight of stearic acid and 1 part by weight of antioxidant 4020 were mixed at 60-100° C. for 15 min, and then 1 part by weight of sulfur was added and mixed at 30-40° C. for 10 min to obtain a mixed rubber containing 10.25 wt% of boron nitride / alumina microspheres;
[0064] Hollow meta-aramid fibers and hollow polyurethane fibers are woven at a mass ratio of 1:3 to obtain a fiber fabric layer 22. The fiber fabric layer 22 has a thickness of 3 mm, an average pore size of 20 μm, and a density of 0.048 g / cm 3 ;
[0065] The mixed rubber is coated on the surface of the fiber fabric layer 22, and is placed in a mold with an S-shaped protrusion. After hot pressing and vulcanization molding, a sound-absorbing layer 2 is obtained in which the fiber fabric layer 22 is coated with the rubber layer 21, and an S-shaped groove is provided on the outer end surface of the inner layer 211 of the rubber layer 21; the inner layer 211 of the rubber layer 21 has a thickness of 2 mm, the outer layer 212 has a thickness of 1 mm, and the two side edges 213 have a thickness of 1 mm. The depth of the S-shaped groove is 1 mm, the width is 2 mm, and the distance between two adjacent S-shaped grooves is 10 mm;
[0066] Adhesive is sprayed on the circumferential inner wall of the tire body 1, and then the sound absorbing layer 2 is bonded to the inner wall of the tire body 1 to obtain a new energy tire. Example 3
[0067] This embodiment produces a new energy tire, which is different from the embodiment 2 in that:
[0068] The amount of boron nitride / alumina microspheres in the meta-aramid spinning solution was changed to 1.38 parts by weight, thereby obtaining hollow meta-aramid fibers containing 19.92 wt % of boron nitride / alumina microspheres.
[0069] The amount of boron nitride / alumina microspheres in the polyurethane spinning solution was changed to 4 parts by mass, thereby obtaining hollow polyurethane fibers containing 20 wt % of boron nitride / alumina microspheres.
[0070] The boron nitride / alumina microspheres in the rubber mix were changed to 26 parts by weight to obtain a rubber mix containing 19.85 wt % of boron nitride / alumina microspheres;
[0071] Hollow meta-aramid fibers and hollow polyurethane fibers are woven at a mass ratio of 1:3 to obtain a fiber fabric layer 22. The fiber fabric layer 22 has an average pore size of 40 μm and a density of 0.030 g / cm 3 . Example 4
[0072] This embodiment produces a new energy tire, which is different from the embodiment 2 in that:
[0073] The boron nitride / alumina microspheres in the meta-aramid spinning solution were changed to 0.98 parts by weight to obtain hollow meta-aramid fibers containing 15.01 wt % of boron nitride / alumina microspheres.
[0074] The amount of boron nitride / alumina microspheres in the polyurethane spinning solution was changed to 2.83 parts by mass, thereby obtaining hollow polyurethane fibers containing 15.03 wt % of boron nitride / alumina microspheres.
[0075] The boron nitride / alumina microspheres in the rubber mix were changed to 19 parts by weight to obtain a rubber mix containing 15.32 wt % of boron nitride / alumina microspheres;
[0076] Hollow meta-aramid fibers and hollow polyurethane fibers are woven at a mass ratio of 1:3 to obtain a fiber fabric layer 22. The fiber fabric layer 22 has an average pore size of 30 μm and a density of 0.039 g / cm 3 . Example 5
[0077] This embodiment produces a new energy tire. The difference from the embodiment 4 is that the hollow meta-aramid fiber and the hollow polyurethane fiber are woven at a mass ratio of 1:1 to obtain a fiber fabric layer 22. The density of the fiber fabric layer 22 is 0.043 g / cm 3 . Example 6
[0078] This embodiment produces a new energy tire. The difference from the embodiment 4 is that the hollow meta-aramid fiber and the hollow polyurethane fiber are woven at a mass ratio of 2:3 to obtain a fiber fabric layer 22. The density of the fiber fabric layer 22 is 0.041 g / cm 3 . Example 7
[0079] This embodiment produces a new energy tire. The difference from the embodiment 4 is that the hollow meta-aramid fiber and the hollow polyurethane fiber are woven at a mass ratio of 1:3 to obtain a fiber fabric layer 22. The fiber fabric layer 22 has a thickness of 15 mm and a density of 0.041 g / cm 3 . Example 8
[0080] This embodiment produces a new energy tire. The difference from the embodiment 4 is that the hollow meta-aramid fiber and the hollow polyurethane fiber are woven at a mass ratio of 1:3 to obtain a fiber fabric layer 22. The fiber fabric layer 22 has a thickness of 9 mm and a density of 0.040 g / cm3 . Example 9
[0081] This embodiment produces a new energy tire, which is different from Example 4 in that the inner layer 211 of the rubber layer 21 is 3 mm thick, the outer layer 212 is 1 mm thick, the two side edges 213 are 1 mm thick, the depth of the S-shaped groove is 2 mm, the width is 3 mm, and the distance between two adjacent S-shaped grooves is 5 mm. Example 10
[0082] This embodiment produces a new energy tire, which is different from Example 4 in that the inner layer 211 of the rubber layer 21 is 1 mm thick, the outer layer 212 is 1 mm thick, the two side edges 213 are 1 mm thick, the depth of the S-shaped groove is 0.5 mm, the width is 1 mm, and the distance between two adjacent S-shaped grooves is 3 mm.
[0083] Comparative Example 1
[0084] This comparative example produces a new energy tire, which differs from Example 4 in that it does not contain the sound absorbing layer 2.
[0085] Comparative Example 2
[0086] This comparative example produces a new energy tire, which is different from Example 4 in that:
[0087] The boron nitride / aluminum oxide microspheres are removed from the meta-aramid spinning solution to obtain hollow meta-aramid fibers without the boron nitride / aluminum oxide microspheres.
[0088] The boron nitride / alumina microspheres are removed from the polyurethane spinning solution to obtain hollow polyurethane fibers without the boron nitride / alumina microspheres.
[0089] removing the boron nitride / alumina microspheres from the rubber mix to obtain a rubber mix free of the boron nitride / alumina microspheres;
[0090] Hollow meta-aramid fibers and hollow polyurethane fibers are woven at a mass ratio of 1:3 to obtain a fiber fabric layer 22. The density of the fiber fabric layer 22 is 0.040 g / cm 3 .
[0091] Comparative Example 3
[0092] This comparative example produces a new energy tire, which is different from Example 4 in that there is no S-shaped groove on the outer end surface of the inner layer 211 of the rubber layer 21.
[0093] Comparative Example 4
[0094] This comparative example produces a new energy tire, which is different from Example 4 in that the rubber layer 21 is removed and the fiber fabric layer 22 is directly bonded to the tire body 1.
[0095] Performance testing:
[0096] The tire noise test method of GB / T32789-2016 was used to measure the tire noise of the new energy tires in Examples 2-10 and Comparative Examples 1-4. The tire pressure was 240 kPa, the tire load was 400 kg, the drum speed was 80 km / h, and the tire cavity noise peak was tested at 200-250 Hz. The test results are shown in Table 1.
[0097]
[0098] As can be seen from Table 1, the new energy tires prepared in Examples 2-10 have excellent sound absorption and noise reduction performance; in Examples 2-10, the noise peak of the new energy tire containing the sound absorbing layer 22 is 55.6-61.1 dB, and the noise peak of the new energy tire without the sound absorbing layer 22 in Comparative Example 1 is 68.8 dB. It can be seen that the setting of the sound absorbing layer 22 greatly improves the sound absorption and noise reduction performance of the new energy tire; Comparative Example 2 is based on Example 4, but the boron nitride / aluminum oxide microspheres in the sound absorbing layer 22 are removed, and its sound absorption performance is much lower than that of Example 4; Comparative Example 3 is based on Example 4, but the S-shaped pattern on the sound absorbing layer 22 is removed, and its sound absorption performance is lower than that of Example 4; Comparative Example 4 is based on Example 4, but the rubber layer 21 is removed, and the sound absorbing layer 22 is directly bonded to the tire body 1, and its sound absorption performance is much lower than that of Example 4.
[0099] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A new energy tire, comprising a tire body (1), characterized in that: A sound absorbing layer (2) is bonded to the inner wall of the tire body (1) in the circumferential direction, the sound absorbing layer (2) comprising a rubber layer (21) and a fiber fabric layer (22), the rubber layer (21) being coated on the surface of the fiber fabric layer (22), and having S-shaped grooves equidistantly arranged at the circumference of the part in contact with the tire body (1); the fiber fabric layer (22) comprising hollow meta-aramid fibers and hollow polyurethane fibers, the rubber layer (21), the hollow meta-aramid fibers and the hollow polyurethane fibers all containing boron nitride / alumina microspheres, the boron nitride / alumina microspheres being hollow microspheres with a core-shell structure having hollow glass microspheres as cores and boron nitride / alumina as shells.
2. A new energy tire according to claim 1, characterized in that: The rubber layer (21) comprises an inner layer (211), an outer layer (212) and two side edges (213); the S-shaped groove extends along the width direction of the inner layer (211), has a depth of 1 / 2 to 2 / 3 of the thickness of the inner layer (211), a width of 1 to 3 mm, and a distance between two adjacent S-shaped grooves of 3 to 10 mm; the thickness ratio of the inner layer (211), the outer layer (212), the side edges (213) and the fiber fabric layer (22) is (1 to 3): 1: 1: (3 to 20); the average pore size of the woven holes of the fiber fabric layer (22) is 2 to 200 μm, and the density is 0.02 to 0.2 g / cm 3 The mass ratio of the hollow meta-aramid fiber to the hollow polyurethane fiber is (1-3):3; the rubber layer (21), the hollow meta-aramid fiber and the hollow polyurethane fiber respectively contain 5-20wt% of boron nitride / alumina microspheres; the mass ratio of boron nitride, alumina and hollow glass microspheres in the boron nitride / alumina microspheres is 1:4:(3-4).
3. The method for producing a new energy tire according to claim 1 or 2, characterized in that: The following steps are involved: Step S100. The rubber matrix, boron nitride / aluminum oxide microspheres, zinc oxide, stearic acid, an antioxidant and a vulcanizing agent are uniformly mixed to obtain a mixed rubber; Step S200. Adding boron nitride / alumina microspheres to a meta-aramid spinning solution, and coaxially spinning the microspheres with the meta-aramid support solution to obtain hollow meta-aramid fibers; adding boron nitride / alumina microspheres to a polyurethane spinning solution, and coaxially spinning the microspheres with the polyurethane support solution to obtain hollow polyurethane fibers; weaving the hollow meta-aramid fibers and the hollow polyurethane fibers to obtain a fiber fabric layer (22); Step S300. The mixed rubber is coated on the surface of the fiber fabric layer (22), placed in a mold with an S-shaped protrusion, and hot-pressed and vulcanized to obtain a sound-absorbing layer (2) in which the fiber fabric layer (22) is coated with a rubber layer (21), and an S-shaped groove is provided on the outer end surface of the inner layer (211) of the rubber layer (21); Step S400: spray adhesive on the circumferential inner wall of the tire body (1), and then bond the sound absorbing layer (2) to the inner wall of the tire body (1) to obtain a new energy tire.
4. The method for producing a new energy tire according to claim 3, characterized in that: In step S100, the rubber matrix is at least one of natural rubber, butadiene rubber, butyl rubber, styrene-butadiene rubber and nitrile rubber; the antioxidant is at least one of antioxidant 4020, antioxidant H and antioxidant D; and the vulcanizing agent is sulfur; During mixing, first mix the rubber matrix, hexagonal boron nitride, nano-aluminum oxide, zinc oxide, stearic acid and antioxidant at 60-110°C for 10-15 minutes, then add the vulcanizing agent, control the temperature at 30-40°C, and continue mixing for 5-10 minutes.
5. The method for producing a new energy tire according to claim 3, characterized in that: In step S100, the mass ratio of the rubber matrix, boron nitride / aluminum oxide microspheres, zinc oxide, stearic acid, antioxidant and vulcanizing agent is 100: (6-26): (1-2): (1-3): (1-2): (1-2); In step S200, the mass ratio of the hollow meta-aramid fiber to the hollow polyurethane fiber is (1-3):
3.
6. The method for producing a new energy tire according to claim 3, characterized in that: In step S100 and step S200, the preparation of the boron nitride / aluminum oxide microspheres comprises the following steps: Step S110. sequentially performing dopamine modification and silver ion modification on the hollow glass microspheres to obtain secondary modified microspheres; Step S120. Add the citric acid aqueous solution to the aluminum nitrate aqueous solution, stir evenly, then add the sodium hydroxide aqueous solution, stir evenly to obtain a first dispersion; add hexagonal boron nitride and secondary modified microbeads to the first dispersion, stir and disperse evenly to obtain a second dispersion; heat the liquid paraffin oil to 55-65° C., then drop the second dispersion into the liquid paraffin oil under stirring, raise the temperature to 90° C. after the dropwise addition is completed, react for 3 hours, and after the reaction is completed, separate and filter to obtain precursor particles; Step S130: calcine the precursor particles at 450°C for 4 hours, then heat to 700°C for 8 hours, and finally calcine at 1200°C under nitrogen protection for 2 hours to obtain boron nitride / aluminum oxide microspheres.
7. The method for producing a new energy tire according to claim 6, characterized in that: The specific steps of step S110 include: Step S111. Immerse the hollow glass microspheres in a dopamine hydrochloride solution with a pH value of 8.5 and a concentration of 2 g / L, stir and react at 40° C. for 24 hours, wash and filter after the reaction to obtain primary modified microspheres; Step S112: Immerse the primary modified microbeads in a 0.05 mol / L silver nitrate solution, stir and react for 1.5 h, wash and filter after the reaction to obtain secondary modified microbeads.
8. The method for producing a new energy tire according to claim 6, characterized in that: In step S110, the hollow glass microspheres are at least one of K37, K90, K85, HX0.35, and HX0.38; In step S120, the mass ratio of citric acid, aluminum nitrate, sodium hydroxide, hexagonal boron nitride and secondary modified microbeads is 10:18:8:20:(15-20); the concentration of the citric acid aqueous solution is 40wt%, the concentration of the aluminum nitrate aqueous solution is 30wt%, and the concentration of the sodium hydroxide aqueous solution is 25wt%; the mass ratio of the second dispersion and liquid paraffin is 1:(4-5).
9. The method for producing a new energy tire according to claim 3, characterized in that: In step S200, the preparation of the hollow meta-aramid fiber and the hollow polyurethane fiber includes the following steps: Step S210. Under nitrogen protection, m-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole are added to dimethylacetamide, and stirred to obtain a first solution; under nitrogen protection at -25 to -15°C, isophthaloyl chloride is added to the first solution in multiple portions to react, the reaction temperature is controlled to be lower than 60°C, and after the reaction is completed, the pH value is adjusted to 6 to 8 to obtain an aramid polymer solution; Step S220. The aramid polymer solution, calcium chloride, polyethylene glycol 2000, boron nitride / alumina microspheres and dimethylacetamide are stirred and mixed uniformly, and a meta-aramid spinning solution is obtained after vacuum degassing; dimethylacetamide, ethanol and deionized water are mixed and stirred uniformly to obtain a meta-aramid support solution; Step S230. Add the meta-aramid spinning solution and the meta-aramid supporting solution into a syringe with a coaxial needle respectively, and inject them into a coagulation bath at 60-80° C. through the syringe for coaxial spinning to obtain aramid primary fibers; wash and dry the aramid primary fibers to obtain hollow meta-aramid fibers containing boron nitride / alumina microspheres; Step S240. Polytetramethylene glycol 2000, polycarbonate diol, 1,4-butanediol, bis(2-hydroxyethyl) disulfide and isophorone diisocyanate are stirred and reacted at 60-90° C. for 1-1.5 hours, and then cooled to 40-50° C. to obtain a prepolymer; Step S250. Stir the prepolymer, polycarbodiimide, boron nitride / alumina microspheres, polyvinyl pyrrolidone and ethyl acetate at 20-40° C. for 1-1.5 hours to obtain a polyurethane spinning solution; mix and stir the ethyl acetate and polyvinyl pyrrolidone to obtain a polyurethane support solution; Step S260. Add the polyurethane spinning solution and the polyurethane supporting solution into a syringe with a coaxial needle respectively, and inject them into a coagulation bath at 50-70° C. through the syringe for coaxial spinning to obtain polyurethane primary fibers; after washing and drying the polyurethane primary fibers, hollow polyurethane fibers containing boron nitride / alumina microspheres are obtained.
10. The method for producing a new energy tire according to claim 9, characterized in that: In step S210, the molar ratio of m-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole and dimethylacetamide is (6-7): (3-4): (60-80); the molar ratio of the sum of the moles of m-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole to isophthaloyl chloride is 1:1; the concentration of the aramid polymer in the aramid polymer solution is 33-38wt%; In step S220, the mass ratio of aramid polymer solution, calcium chloride, polyethylene glycol 2000, boron nitride / alumina microspheres and dimethylacetamide is 15:1:1:(0.5-1.5):(20-25); the mass ratio of dimethylacetamide, ethanol and deionized water is 60:10:30; In step S230, the coaxial needle model is 22G / 17G, and the injection speed is 0.03mm / s; the coagulation bath contains 20wt% DMF and 80wt% deionized water; the hollow meta-aramid fiber contains 5-20wt% boron nitride / alumina microspheres; In step S240, the mass ratio of polytetramethylene glycol 2000, polycarbonate glycol, 1,4-butanediol, bis(2-hydroxyethyl) disulfide and isophorone diisocyanate is (60-70):(5-10):(0.5-1):(1-3):40; In step S250, the mass ratio of the prepolymer, polycarbodiimide, boron nitride / alumina microspheres, polyvinyl pyrrolidone and ethyl acetate in the spinning solution is 15: (0.5-1): (1.5-4): (1-2): (20-30); the mass ratio of ethyl acetate and polyvinyl pyrrolidone in the spinning core solution is 2:1; In step S260, the coaxial needle model is 22G / 17G, the injection speed is 0.03 mm / s; the coagulation bath is deionized water; and the hollow polyurethane fiber contains 5 to 20 wt% of boron nitride / alumina microspheres.
Citation Information
Patent Citations
Tire noise reduction device and production method thereof
CN110001310A
Pneumatic radial tire
CA1170556A
Preparation method of sound-absorbing rubber
CN106397879A